THE PERINATAL ANXIETY SCREENING SCALE (PASS) ASSESSMENT OF HIGHRISK PREGNANT WOMEN - Mardianingsih, Siti; Mutianingsih, Rosa; Abdiani, Baiq Tuhu; fatawi, zulhadi (UNIVERSITAS AIRLANGGA, 2024)
Background: Psychological changes in pregnant women can be caused by hormonal imbalances. Imbalance can give rise to an anxiety response caused by conditions within oneself and the environment. Excessive anxiety can stimulate uterine contractions which can lead to pathological risks in the pregnancy. The aim of this research is to determine the anxiety and psychological domains of high-risk pregnant women. Method: The research design was descriptive research with a sample size of 30 pregnant women who had a history of high risk in Batu Kute village, Narmada subdistrict using cluster sampling technique. The instrument used was the PASS (perinatal anxiety screening scale) questionnaire. Result: The research results obtained were that most pregnant women experienced anxiety on a mild - moderate scale with a percentage of 70% experienced by mothers in the first and third trimesters of pregnancy. is in the domain category of excessive worry and specific fear as much as 57% and anxiety and active adjustment as much as 23.3%. The level of anxiety of pregnant women in the first trimester is due to the adaptation process to changes in a woman and will increasingly increase in the third trimester of pregnancy leading up to delivery. Conclusion: Anxiety conditions with or without previous symptoms will increase in high-risk third trimester mothers because they feel anxious about the condition of themselves and their fetus. If not treated, it will pose a risk to the mother, fetus and the birth process that will occur.